A comparison of in-service and pre-service teachers’ technological pedagogical content knowledge self-confidence - Fatih Saltan; Kürşat Arslan (Cogent Education, 2017)
This study aimed to investigate and compare in-service and pre-service teachers’ self confidence on technological pedagogical content knowledge (TPACK) in relation to their teaching experience, expertise, technology usage, and gender. To achieve this goal, survey method was conducted as part of a quantitative method design. Participants of the study consisted of 388 pre-service and 211 in-service teachers from four different concentrations: science, mathematics, information, and communications technology (ICT) and classroom teachers. The data were analyzed using paired Sample T-test and MANOVA statistical analysis. Results showed that both pre-service and in-service participants exhibit the highest self-confidence level in the technological content knowledge domain. While pre-service teachers had the lowest score in TPACK, in-service teachers had the lowest score in the technological knowledge domain. While pre-service mathematics teachers have significantly lower TPACK than pre-service science teachers, in-service ICT teachers’ TPACK level is significantly higher than science, math, and classroom teachers’ levels considering TPACK, pedagogical content knowledge (PCK) and technology knowledge (TK) domains.